Environmental impact of national and subnational carbon policies in China based on a multi-regional dynamic CGE model. (15th September 2020) - Zhang, Wen-Wen; Zhao, Bin; Gu, Yu; Sharp, Basil; Xu, Shi-Chun; Liou, Kuo-Nan
Abstract: Carbon policies are important not only for mitigating global climate change, but also for controlling local and regional air pollution. The large regional disparities in economic development and air pollution across China calls for regionally differentiated policies. Previous studies have not systematically investigated the environmental impacts of regional carbon policies in China covering different spatial scales. This study constructs a multi-regional dynamic computable general equilibrium (CGE) model covering 30 provinces of China to assess the impacts of national and subnational carbon polices on CO2 emissions and co-emitted air pollutants from 2020 to 2050. We consider one national carbon policy which aims to achieve China's 2030 national CO2 abatement target, as well as three regional policies with the same policy stringency as the national one but only applied to eastern China (EP), the Jiangsu-Shanghai-Zhejiang area (JSZP), and the Beijing-Tianjin-Hebei area (BTHP), respectively. We find that regional policies (EP, JSZP, and BTHP) are as effective in reducing CO2 emissions in their targeted regions as the national policy. However, they lead to an increase in CO2 emissions in untargeted regions (the so-called "emissions leakage"). The CO2 leakage rates, which depend on the policy spatial coverage, are 4%, 13%, and 65% for EP, JSZP, and BTHP, respectively, in 2050. Compared with CO2, changes in air pollutant emissions, including sulfur dioxide (SO2 ), nitrogen oxides (NOx ), volatile organic compounds (VOC), and fine particulate matter (PM2.5 ), exhibit a similar pattern under all policy scenarios, but the magnitude of change is significantly smaller. Transportation, thermal power, and some energy intensive industries are the three largest contributors to CO2 and air pollutant emission reductions. Our results suggest that regional carbon policy is effective in reducing CO2 and air pollutant emissions in the targeted regions, and extending the spatial coverage or increasing policy stringency can largely inhibit emissions leakage. Highlights: We examine effects of subnational carbon policies on CO2 and co-emitted pollutants. A multi-regional dynamic CGE model covering China's 30 provinces is constructed. Subnational policies are as effective in their targeted regions as the national one. Subnational policies lead to emission leakage to untargeted regions. Extending spatial coverage or increasing policy stringency inhibits emission leakage.